2014
DOI: 10.1155/2014/928507
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Simulated and Real Microgravity on Bone Cells and Mesenchymal Stem Cells

Abstract: How microgravity affects the biology of human cells and the formation of 3D cell cultures in real and simulated microgravity (r- and s-µg) is currently a hot topic in biomedicine. In r- and s-µg, various cell types were found to form 3D structures. This review will focus on the current knowledge of tissue engineering in space and on Earth using systems such as the random positioning machine (RPM), the 2D-clinostat, or the NASA-developed rotating wall vessel bioreactor (RWV) to create tissue from bone, tumor, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 157 publications
(152 reference statements)
0
63
0
Order By: Relevance
“…A role for the autophagic control of osteoclastogenesis in response to microgravity has been proposed for mouse bone (Sambandam et al, 2014). A recent review by Ulbrich et al (2014) details the impact of simulated and real microgravity on bone and mesenchymal cells and their osteogenic potential.…”
Section: Microgravity Adult Stem Cells and Tissue Renewalmentioning
confidence: 99%
“…A role for the autophagic control of osteoclastogenesis in response to microgravity has been proposed for mouse bone (Sambandam et al, 2014). A recent review by Ulbrich et al (2014) details the impact of simulated and real microgravity on bone and mesenchymal cells and their osteogenic potential.…”
Section: Microgravity Adult Stem Cells and Tissue Renewalmentioning
confidence: 99%
“…138 Cosmic radiation can affect any cell in space, from in vitro cultures to whole organisms, where radiation may directly or indirectly contribute to the development of any microgravity-associated conditions including bone loss 139 and immune suppression by T-cell and macrophage deactivation. 140 Although s-μg and real-μg studies are increasingly being compared for validation, 6,141 cosmic radiation must be emulated in ground based studies for more meaningful comparison and to better study the potentially synergistic biological effects of ionizing radiation and microgravity. For example, Shanmugajaran et al found potentially additive effects of low doses of radiation (0.1-0.5 Gy) and s-μg on osteoclast fusion whereas the synergy was offset by higher radiation doses above 0.5 Gy.…”
Section: Comparability Of S-g Studies With Conditions In Spacementioning
confidence: 99%
“…Extracellular signal-regulated kinase (ERK) pathway may also be involved in this regulation (Hu et al 2013a;Hu et al 2015). For MSCs, studies on STS (space transportation system) project during spaceflight and other SMs on the ground reveal that apoptosis, cytoskeleton disruption and osteogenic differentiation inhibition are caused under microgravity (Blaber et al 2014;Ulbrich et al 2014). Besides, microgravity strongly inhibits osteoblastogenesis and increases adipocyte differentiation in MSCs (Rodriguez et al 2008).…”
Section: Mechanotransduction Of Bone and Immune Cells Under Microgravitymentioning
confidence: 99%